2023
DOI: 10.3390/ma16020502
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Plasma in Ultrasonic-Assisted Narrow-Gap Laser Welding with Filler Wire

Abstract: Laser welding with filler wire was applied to Q345D in a narrow gap under ultrasonic assistance, and the dynamic characteristics of plasma were studied by high-speed imaging and spectral acquisition. The results showed that the plasma area decreased gradually with increasing distance between the ultrasonic loading position and welding seam. The electron density and temperature of the plasma with ultrasonic assistance were higher than those without ultrasound. The electron density was approximately 1016~1017 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kovalev et al,in [13], discussed different methods for producing light-trapping "black" silicon, namely laser, chemical and hybrid chemical/laser. Wang et al,in [14], presented the results of a study where a steel plate was welded by ultrasonic-assisted narrow-gap laser welding with a filler wire, and the plasma was observed using a high-speed camera and spectrograph. Fu et al,in [15], presented a research study in which duplex stainless steel was welded by alternating a magnetic field with a laser-arc.…”
Section: Resultsmentioning
confidence: 99%
“…Kovalev et al,in [13], discussed different methods for producing light-trapping "black" silicon, namely laser, chemical and hybrid chemical/laser. Wang et al,in [14], presented the results of a study where a steel plate was welded by ultrasonic-assisted narrow-gap laser welding with a filler wire, and the plasma was observed using a high-speed camera and spectrograph. Fu et al,in [15], presented a research study in which duplex stainless steel was welded by alternating a magnetic field with a laser-arc.…”
Section: Resultsmentioning
confidence: 99%
“…Through a large number of experiments, Long et al [ 10 ] found that the key to solve the incomplete fusion was the ratio of the welding line energy to the wire feed. Wang et al [ 11 ] reduced the porosity defects effectively with ultrasonic assistance and found that the electron temperature and density of the laser-induced plasma increased [ 12 ]. Jiang et al [ 13 ] found that laser oscillation brought a strong stirring effect, which changed the growth pattern of the sidewall grain and reduced the porosity defects.…”
Section: Introductionmentioning
confidence: 99%